Chapter Maritime Information Networks between Northern and Southern Europe during the Eighteenth century - Ojala, Jari (Atti delle «Settimane di Studi» e altri Convegni, 2019)
International trade during the 18th century is a case in point through which to study in-depth the challenges of asymmetric information. The challenges can be divided into three categories: availability, reliability and usability of information. This article discusses the organization of trade and shipping between Northern and Southern Europe. The access, reliability and use of information were problems for merchant-shipowners during the 18th century. The solutions adopted were partly contradictory: the aim to reduce information asymmetry on one determinant, might incur costs on the other.